A Bibliometric Analysis of Zakat Literature from 1964 to 2021 - Indri Supriani; Sri Iswati; Firsty Izzata Bella; Yunice Karina Tumewang (Muhammadiyah University Press, 2022)
This research is intended to provide a comprehensive historical and present development of zakat literature through bibliometrics analysis extracted from Scopus database. From 522 articles related to zakat, the findings show that Universiti Utara Malaysia, IMEFM, and Saad, R. A. J have become the most institution, journal and author that published in zakah literature respectively. Moreover, the article from Haniffa, R; Hudaib (2007) is found to be the most cited article worldwide. While Malaysia has become the hub center of the research collaboration network with a strong collaboration with Indonesian researchers.